Epigenetic biomarkers of promoter DNA methylation in the new era of cancer treatment. Issue 12 (26th October 2018) - Yamashita, Keishi; Hosoda, Kei; Nishizawa, Nobuyuki; Katoh, Hiroshi; Watanabe, Masahiko
Abstract : Promoter DNA methylation, which occurs on cytosine nucleotides across CpG islands, results in gene silencing and represents a major epigenetic alteration in human cancer. Methylation‐specific PCR can amplify these modifications as markers in cancer cells. In the present work, we rigorously review the published literatures describing DNA methylation in the promoters of critical tumor suppressor genes; detection of promoter DNA methylation in various body fluids permits early detection of cancer cells during perioperative courses of clinical treatment. The latest whole‐genome comprehensive explorations identified excellent epigenetic biomarkers that could be detected at high frequency with high specificity; these biomarkers, which are designated highly relevant methylation genes (HRMG), permit the discrimination of tumor tissues from the corresponding normal tissues; these markers are also associated with unique cancer phenotypes, including dismal prognosis. In humans, HRMG include the CDO1, GSHR, RASSF1 and SFRP1 genes, with these markers permitting discrimination depending on the organs tested. The combination of several HRMG increased the early detection of cancer and exhibited reliable surveillance potential in human body fluids. Cancer clinics using such epigenetic biomarkers are entering a new era of enhanced decision‐making with the potential for improved cancer prognosis. Abstract : This is a review paper describing molecular diagnostics of cancer using DNA methylation. DNA methylation has been recently focused on in relation to liquid biopsy in various cancers. It is a promising candidate to improve cancer treatment and patient prognosis.